P028 Transitioning patients from intravenous to subcutaneous infliximab and vedolizumab for inflammatory bowel disease – what is the opportunity cost of improving access to health care?. (30th January 2023) - Hilley, P; Wong, D; Ma, R; Peterson, A; De Cruz, P
Abstract: Background: Biologic drugs are highly effective for inflammatory bowel disease (IBD) management but are key drivers of costs of care especially when administered intravenously (IV). Availability of subcutaneous (SC) formulations has increased convenience for patients and improved access to care but at the cost of revenue to health services. The aim of this study was to evaluate the economic impact of transitioning a tertiary centre IBD cohort from IV to SC biologic administration and assess the implications for key stakeholders. Methods: A retrospective analysis of all patients that received IV infliximab or vedolizumab in the outpatient infusion centre of a tertiary, IBD centre between July 2019 and June 2021 was undertaken. Data were extracted from electronic medical records, pharmacy dispensing systems and the hospital business intelligence unit. An economic analysis and theoretical financial/capacity impact analysis of a transition to a SC model was estimated under two theoretical scenarios, using a random 10% and 30% of the patient cohort. Results: Transitioning our IBD cohort from IV to SC administration would result in a loss of 2, 732, 123.75, comprised of 1, 463, 003.75 in Weighted Inlier Equivalent Separation (WIES) and 1, 269, 120 in drug procurement revenue. However, it would ease capacity in the infusion centre by up to 5256 hours. Conclusion: Transitioning patients to SC administration results in improved access to infusion centres and substantial savings to state governments; however, switching results in a loss of IV-biologic generated WIES to health services. Alternative funding models are required to achieve sustainability in IBD care and reduce reliance on IV biologic generated income.